Ethics of Socially Disruptive Technologies 2023
DOI: 10.11647/obp.0366.06
|View full text |Cite
|
Sign up to set email alerts
|

6. Conceptual Disruption and the Ethics of Technology

Jeroen Hopster,
Philip Brey,
Michael Klenk
et al.

Abstract: This chapter provides a theoretical lens on conceptual disruption. It offers a typology of conceptual disruption, discusses its relation to conceptual engineering, and sketches a programmatic view of the implications of conceptual disruption for the ethics of technology. We begin by distinguishing between three different kinds of conceptual disruptions: conceptual gaps, conceptual overlaps, and conceptual misalignments. Subsequently, we distinguish between different mechanisms of conceptual disruption, and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…This inevitably comes with transformations of traditional ethical concepts. Elsewhere in research, it has already been shown that with the advent of emerging technologies like robots, our ethical concepts are being disrupted and transformed (Van de Poel et al, 2023a;Van de Poel et al, 2023b;Hopster et al, 2023).…”
Section: Consequences For Robot Ethicsmentioning
confidence: 99%
“…This inevitably comes with transformations of traditional ethical concepts. Elsewhere in research, it has already been shown that with the advent of emerging technologies like robots, our ethical concepts are being disrupted and transformed (Van de Poel et al, 2023a;Van de Poel et al, 2023b;Hopster et al, 2023).…”
Section: Consequences For Robot Ethicsmentioning
confidence: 99%